Virulence Traits and Antimicrobial Sensitivity Testing of Untyped Mycoplasma species Recovered from Sheep and Goat in Egypt - Mona, M. Osman (Egyptian Society for Animal Management, 2021)
Many Mycoplasma species are involved in caprine and ovine pneumonia all over the world causing serious economic losses. These species have been reported to cause pneumonia, mastitis, arthritis, conjunctivitis and genital infection. The objective of the present study was to detect Mycoplasma species in the respiratory system of sheep and goats. So, a total of 400 samples (250 from sheep and 150 from goat) were examined bacteriologically, biochemically, by PCR, sequencing, in addition to the antibiotic susceptibility profiles screening. Only 13 isolates could be identified as Mycoplasma species. One of these sequences was submitted to the Genbank taking the accession number MK910041; Mycoplasma species 'ovine/caprine serogroup 11'. Only 7 isolates were weak biofilm producers and the other 6 isolates were non biofilm producers; 8 isolates were positive for the catalase test and 5 were negative. H2S production was recorded in 10 isolates; haemolysis was detected in only 6 isolates. In addition, the minimum inhibitory concentrations (MICs) for seven antimicrobial agents, including danofloxacin, tulathromycin, tylosin, streptomycin, lincomycin, florfenicol and oxytetracycline, were determined. All the isolates (100%) were sensitive to tulathromycin and tylosin, streptomycin and oxytetracycline; 38.5% were sensitive to danofloxacin, 69.2% were sensitive to florfenicol, while 69.2% of isolates were resistant to lincomycin. As all the isolates were recovered from apparently healthy and clinically diseased animals and identified as untyped Mycoplasma species, more investigations will be done to identify these isolates and discover their roles in infection.